Identifying dominant recombination mechanisms in spiro-based conventional perovskite solar cells: Roles of interface and bulk recombination. (November 2022) - Parikh, Nishi; Pandey, Manoj; Kumar, Manoj; Prochowicz, Daniel; Kalam, Abul; Tavakoli, Mohammad Mahdi; Satapathi, Soumitra; Yadav, Pankaj
Abstract: Perovskite solar cells (PSCs) have been popular in the photovoltaic (PV) community, owing to their ease of processing and high efficiency. In order to improve their device performance, the interfaces are believed to play a vital role. In this regard, the interfacial energies and the associated physical processes such as charge transport, accumulation and recombination have been the focus of the research community. Despite the rise in power conversion efficiency (PCE) and all development, PSCs still suffer from the charge carrier recombination. As a result, highly efficient PSCs cannot meet the theoretical values of fill factor (FF) and open-circuit voltage ( V OC ). Therefore, to reach out to the theoretical limit of performance for PSCs, carrier recombination needs to be controlled both in the bulk and at the corresponding interfaces. Herein, we have systematically studied the recombination in PSCs by establishing the role of different layers of PSCs using electrochemical impedance spectroscopy (EIS). To get insights into the role of different layers in recombination we fabricated PSCs with n-i-p configuration and changed the thickness of TiO 2 electron transport layer (ETL), absorber layer, and spiro-OMeTAD hole transport layer (HTL). Our results suggest that the recombination is reduced in case of devices with thicker HTL and is trap-assisted recombination. These results are in good agreement with impedance spectroscopy analysis. The value of recombination resistance (extracted by fitting of Nyquist response) is higher at V OC, which is consistent with higher V OC in these two cases. In case of the increased ETL thickness, the performance of the device is dropped since the increased interfacial resistance encourages the recombination. Our study presents a simple and effective approach to elucidate the dominating recombination sites in PSCs and improve the device performance.